A Novel Technique for Prevention of Subarachnoid-Pleural Fistula After Incidental Durotomy During Transthoracic Spinal Surgery. Issue 4 (21st July 2018) - He, Kevin D; Rymarczuk, George N; Clark, Shannon W; Gillick, John L; Vahedi, Payman; Sharan, Ashwini D
Abstract: BACKGROUND: Subarachnoid-pleural fistulas (SPFs) are rare but significant complications of transthoracic spinal surgery. Whether noted intraoperatively or in the postoperative period, SPF requires implementation of aggressive management, with consideration given to direct surgical repair. Additionally, the physical constraints of the thoracic cavity often hinder direct SPF repair. OBJECTIVE: To present a novel operative technique that can be used to easily and quickly address incidental durotomy incurred during transthoracic spinal surgery while working within the confines of the thorax. METHODS: Surgical hemostatic clips were used to affix a patch-graft of dural substitute to the parietal pleura surrounding the site of a transthoracic spinal decompression in which an incidental durotomy was incurred. The patch-graft was augmented with the application of biological glue and was successful in preventing symptomatic SPF. RESULTS: The use of surgical clips to affix a patch graft is a quick, easy, and effective means of addressing an incidental durotomy during thoracotomy and preventing SPF. The clip applier is significantly easier to maneuver within the narrow working channel of the thorax than are instruments used during direct repair. CONCLUSION: Preventing SPF can be challenging. The physical constraints of the thoracic cavity make water-tight repair difficult and time-consuming, particularly when the morphology of the dural tear prevents primary apposition of the defect. The authors present a novel technique of preventing development of SPF using hemostatic clips to simply and quickly affix suturable dural substitute to the parietal pleura overlying the site of an incidental durotomy.